Origin and Diversification of Meprin Proteases. - Ignacio Marín (PLoS ONE, 2015)
Meprins are astacin metalloproteases with a characteristic, easily recognizable structure, given that they are the only proteases with both MAM and MATH domains plus a transmembrane region. So far assumed to be vertebrate-specific, it is shown here, using a combination of evolutionary and genomic analyses, that meprins originated before the urochordates/vertebrates split. In particular, three genes encoding structurally typical meprin proteins are arranged in tandem in the genome of the urochordate Ciona intestinalis. Phylogenetic analyses showed that the protease and MATH domains present in the meprin-like proteins encoded by the Ciona genes are very similar in sequence to the domains found in vertebrate meprins, which supports them having a common origin. While many vertebrates have the two canonical meprin-encoding genes orthologous to human MEP1A and MEP1B (which respectively encode for the proteins known as meprin α and meprin β), a single gene has been found so far in the genome of the chondrichthyan fish Callorhinchus milii, and additional meprin-encoding genes are present in some species. Particularly, a group of bony fish species have genes encoding highly divergent meprins, here named meprin-F. Genes encoding meprin-F proteins, derived from MEP1B genes, are abundant in some species, as the Amazon molly, Poecilia formosa, which has 7 of them. Finally, it is confirmed that the MATH domains of meprins are very similar to the ones in TRAF ubiquitin ligases, which suggests that meprins originated when protease and TRAF E3-encoding sequences were combined.